2020
DOI: 10.3390/su12020661
|View full text |Cite
|
Sign up to set email alerts
|

Land-Use and Legislation-Based Methodology for the Implementation of Sustainable Drainage Systems in the Semi-Arid Region of Brazil

Abstract: In developing countries, the urbanisation process occurs with empirical urban management, a high increase of impermeable areas, and a lack of connection between water resource management and planning. In Brazil, concentrated rainfall and ineffective urban drainage systems add to this context and may impact the population with flash floods. Although sustainable drainage systems (SuDS) are widely used for flood mitigation, it is still not very well known how those strategies behave in semi-arid regions, where mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…However, flooding cases are seen spatially dispersed in different areas of the city (Figure 1(b)), not only in the 'risk areas', which suggests there is a need for developing more accurate information for effective management (Alves et al 2018). The middle-sized city (IBGE 2018) lacks in having sufficient flooding preparedness strategies for the population (Alves et al 2020; and has a weak integration of urban planning and water resources management (de Araújo Grangeiro, Ribeiro, and de Miranda 2019).…”
Section: Study Casementioning
confidence: 99%
See 1 more Smart Citation
“…However, flooding cases are seen spatially dispersed in different areas of the city (Figure 1(b)), not only in the 'risk areas', which suggests there is a need for developing more accurate information for effective management (Alves et al 2018). The middle-sized city (IBGE 2018) lacks in having sufficient flooding preparedness strategies for the population (Alves et al 2020; and has a weak integration of urban planning and water resources management (de Araújo Grangeiro, Ribeiro, and de Miranda 2019).…”
Section: Study Casementioning
confidence: 99%
“…In the Brazilian context, a weak inspection of the legislation fulfilment is seen in different cities. The Master Plan of Campina Grande regulates the maximum imperviousness of 80% of the area in each lot; however, this threshold is often exceeded by residents without any consequence (Alves et al 2020) (i.e. see Alves et al (2020) for a complete legislation analysis).…”
Section: Aspects Generating the Flood Vulnerabilitymentioning
confidence: 99%
“…These strategies are a compelling necessity in the current climatic change context, especially in arid and semi-arid zones. Land-use based modeling was applied at the simulation level to a semi-arid region of Brazil, and it was found that green infrastructure strategies would reduce flooded areas and impacts [71,72]. According to Barros-Ramalho-Alves et al [72], such prediction methodologies can support both long-term urban planning and water resource management.…”
Section: Green Infrastructurementioning
confidence: 99%
“…Land-use based modeling was applied at the simulation level to a semi-arid region of Brazil, and it was found that green infrastructure strategies would reduce flooded areas and impacts [71,72]. According to Barros-Ramalho-Alves et al [72], such prediction methodologies can support both long-term urban planning and water resource management. Lastly, the parameters proposed in this study (T r , T c , Q, R t and R e ) may be useful for the design and planning of sustainable stormwater infrastructure in new developments in urban areas with no precise rainfall information (hourly rainfall, rainfall intensity).…”
Section: Green Infrastructurementioning
confidence: 99%
“…The context will generate specific challenges that will need to be managed effectively to implement NBS (Raymond et al 2017a(Raymond et al , 2017b. The first barrier for applying NBS is based on the understanding that context affects performance directly since they are significantly influenced by hazards intensities (Qin et al 2013), placement (Passeport et al 2013Ahmed et al 2017), climate (Alves et al 2020d), land use (Martin-Mikle et al 2015) and social inequalities (Heckert & Rosan 2018). This suggests there is no 'one-size-fits-all' approach that can be applied everywhere (Colléony & Shwartz 2019) and that the lack of 'locally-oriented' information can harm NBS proposal (Nesshover et al 2017).…”
Section: Introductionmentioning
confidence: 99%